Reflecting on female academics’ narratives on communication strategies in higher education institutions - Mabidi, Ndamulelo Innocentia (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Higher education institutions across South Africa and globally have implemented various strategies to support female academics. These initiatives aim to address gender disparities by fostering mentorship, collaboration, and career development opportunities specifically designed for women. They also seek to enhance publishing rates, employee retention, and engagement. However, achieving a balance between these objectives and the realities of working in historically male-dominated environments remains challenging. Recent research has highlighted the increased responsibilities placed on women during the COVID-19 pandemic, as they had to navigate remote work while managing family care and meeting professional deadlines. Black Feminist Thought and Khan’s Model of Engagement are utilised as appropriate frameworks for exploring the narratives of female academics in higher education institutions. The study conducted a systematic literature review to explore the persistent disparities and systemic barriers women face in South African higher education institutions. Thus, the researcher used Google Scholar, EBSCOhost, ResearchGate, ScienceDirect, Scopus, Sabinet, and Taylor & Francis to retrieve and analyse information from scholarly documents published between 2014 and 2024. The study contributes to the broader discourse on transforming education and amplifying the voices of marginalised individuals within academic settings.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 9, 2025 Special Issue
Keywords: Gender equity; Communication strategies; Higher education institutions in South Africa; Women in higher education; Universities and colleges; Women in higher education; Gender identity in education; Communication in education -- South Africa